2012
DOI: 10.1002/acr.21810
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in assessment of obesity in rheumatoid arthritis

Abstract: Objective Determine prevalence of obesity and how accurately standard anthropometric measures identify obesity among men and women with RA. Methods Dual-energy x-ray absorptiometry (DXA) was performed for 141 persons with RA (56 men, 85 women). Two anthropometric proxies of obesity (body mass index [BMI], waist circumference [WC]) were compared to a DXA-based obesity criterion. Receiver operating characteristic (ROC) curves determined optimal cut-points for each anthropometric measure, relative to DXA. Assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 42 publications
1
40
0
Order By: Relevance
“…(14-16) For example, we previously reported that men with RA were at greater risk of obesity, compared with women. (12) Similarly, two previous studies demonstrated significantly lower estimates of lean body mass in men with RA compared to matched controls, but this association was absent in women. (10, 17) Despite these observations, assessment of sex differences in the extent of lean mass deficits among men and women has been limited by the lack of robust sex-specific reference ranges and consideration of sex differences in risk factors for abnormal body composition.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…(14-16) For example, we previously reported that men with RA were at greater risk of obesity, compared with women. (12) Similarly, two previous studies demonstrated significantly lower estimates of lean body mass in men with RA compared to matched controls, but this association was absent in women. (10, 17) Despite these observations, assessment of sex differences in the extent of lean mass deficits among men and women has been limited by the lack of robust sex-specific reference ranges and consideration of sex differences in risk factors for abnormal body composition.…”
mentioning
confidence: 63%
“…Details of the cohort have previously been published. (12) Briefly, the majority of the research participants in this dataset were drawn from the University of California, San Francisco (UCSF) RA Panel Study. After telephone interviews in the study years 2007–2009, RA Panel participants who lived in the greater San Francisco area were recruited for in-person assessments, including measurement of body composition.…”
Section: Methodsmentioning
confidence: 99%
“…Stavropoulos-Kalinoglou et al (21) and Katz et al (22) suggested new RA-specific BMI cut-off points that are lower than the current WHO cut-off values, therefore classifying an even larger proportion of RA patients as overweight and obese. However, standard anthropometric measurements, including body weight and BMI, are insensitive to demonstrating the changes in body composition that often occur in (weight-stable) RA patients (23).…”
Section: Discussionmentioning
confidence: 98%
“…Details of this cohort are reported by Katz et al [12]. Briefly, participants for this cohort were drawn primarily from the UCSF RA Panel study.…”
Section: Methodsmentioning
confidence: 99%